Application of Restorative Justice Values in Settling Medical Malpractice Cases - Syauf, Ahmad; Haiti, Diana; Mursidah (International Journal of Criminology and Sociology, 2021)
Lawsuits submitted by patients or their families to the hospital and / or their doctors can take the form of criminal or civil lawsuits by almost always basing on the theory of negligence. This paper seeks to explore the application of the values of restorative justice in resolving cases of medical malpractice in Indonesia. This research is a qualitative research using normative legal research and uses a statute approach and a conceptual approach. The results showed that settlement of medical malpractice cases through a restorative justice approach or which is known in the culture of the Indonesian people as a consensus agreement as contained in the 4th Precepts of Pancasila is one alternative settlement that is to restore conflict to the parties most affected (victims, perpetrators and interests community) and give priority to the interests of all parties. The conclusion showed that the restorative justice emphasizes human rights and the need to recognize the impact of social injustice and in simple ways to restore the parties to their original condition rather than simply giving formal justice actors or legal actors and victims not getting any justice. Hence, restorative justice also strives to restore the security of victims, personal respect, dignity and more importantly is a sense of control so as to avoid feelings of revenge both individual or family or group.